Floating Inductance and FDNR Using Positive Polarity Current Conveyors - K. Pal (Active and Passive Electronic Components)
A generalized circuit based on five positive polarity second-generation current conveyors is introduced. The circuit simulates a floating inductance, capacitor floatation circuit and floating fdnr. All these circuits use grounded capacitors.